Development of hiking games technical group guidance module to improve resilience for vocational school students - Ambarwati; Wangid, Muhammad Nur (Universitas Ahmad Dahlan, 2024)
The aim of developing the group guidance module with the hiking game technique is to increase personal resilience and determine the quality of the group guidance module with the hiking game technique as an innovation in guidance and counselling services—Borg & Gall's research and development method in this research. Sukmadinata's modification consists of three stages: preliminary study, model development, and model testing. The research results are a group guidance module on climbing game techniques to increase self-resilience—validation tests to determine the product's feasibility. Three experts validated the results: material, media, and service experts. The results of expert validation obtained data that stated that the group guidance module with the hiking game technique was in the